Incorporation of crumb rubber and air-entraining agent in ultra-lightweight cementitious composite: Evaluation of mechanical and acoustic properties. (October 2021) - Leong, Geok Wen; Chin, Tze Ming; Mo, Kim Hung; Ibrahim, Zainah; Putra, Azma; Othman, Muhammad Nur
Abstract: This research describes the usage of crumb rubber (CR) and air-entraining agent (AEA) to further reduce the density of lightweight cementitious composite into ultra-lightweight cementitious composites (ULCC), which has density lower than 800 kg/m 3 . The effects of CR and AEA on workability, compressive strength, flexural strength, sound absorption and sound transmission loss of ULCC are evaluated. The dry densities of the ULCC produced are in the range of 711–857 kg/m 3 . Compared with the control mix, the addition of 1% of AEA and inclusion 15% of CR have similar effect in reducing the density of ULCC, where the density is reduced by about 15%. Despite the decreased mechanical strength with the use of CR, the ULCC still possess good flexural strength of 2.4 MPa without AEA. Furthermore, the effect of CR is more significant than AEA in improving the sound absorption average (SAA) of ULCC which the SAA of the control mix is increased by 61.3%. Overall, the combination of CR and AEA reduced the density and improved the acoustic performance of ULCC. Highlight: With CR and AEA, ULCC with reduced density of 711–777 kg/m 3 can be obtained. ULCC developed has good flexural/compressive strength ratio despite the low density. Partially replacing 15% PM with CR reduce the brittleness of ULCC. CR is more effective than AEA in improving the sound absorption of ULCC.